1990
DOI: 10.1055/s-2007-998187
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossusparese nach Tonsillektomie*

Abstract: Lesions of the lingual nerve and the glossopharyngeal nerve following tonsillectomy are rare but can be expected because of their anatomical course. What is extremely rare is a lesion of the hypoglossal nerve, whose course behind the carotid artery protects it from direct injury. The few cases described in the literature are thought to have been caused by inflammatory processes. It became necessary to look for other causes when, after a regular tonsillectomy, a hypoglossal palsy became evident in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Michel and Brusis [15] seemed to confirm this idea, identifying the MLS procedure, and especially neck extension to considerably stretch the lingual, glossopharyngeal, and even the hypoglossal nerve in certain cases. Their findings might also explain why sometimes even orotracheal intubation has been claimed to cause cranial nerve injuries (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Michel and Brusis [15] seemed to confirm this idea, identifying the MLS procedure, and especially neck extension to considerably stretch the lingual, glossopharyngeal, and even the hypoglossal nerve in certain cases. Their findings might also explain why sometimes even orotracheal intubation has been claimed to cause cranial nerve injuries (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…However, based on case reports [6] and anatomical studies [15] there were reasons to believe that even quantitative changes of gustatory function may occur more frequently after MLS than is usually assumed. Michel and Brusis [15] seemed to confirm this idea, identifying the MLS procedure, and especially neck extension to considerably stretch the lingual, glossopharyngeal, and even the hypoglossal nerve in certain cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported complete resolution 1 year after diagnosis, 6,9,12,14,20,22 while others found only partial recovery at variable follow-up periods. 1,15,33,49 Five patients (8.3%) had persistent tongue deviation and dysarthria at follow-up intervals. The follow-up interval was not reported for four additional patients with persistent symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, direct pressure exerted by the Macintosh blade at the base of the tongue causes soft tissue compression against the hyoid bone, possibly exacerbating the neurapraxia. 1,3,12,15,26,30,46,49,73,74 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation